The Judges Legal Reasoning on Child Welfare’s Perspective in the Hadanah Cases at Banten Religious Courts - Farida Nurun Nazah; Muslimin Muslimin (Jurnal Hukum, 2024)
This research analyzes the interpretation of the children welfare values in the juridical, sociological and philosophical perspective towards the judges legal reasoning in the hadanah cases at Banten Religious Courts. This research is classified as juridical normative research align with the qualitative descriptive data analysis towards the law approach as well as the Religious Courts Decision approach concerning the divorce and custody that had the legal impact for hadanah. The research result indicates that the hadanah cases decided by Judges legal reasoning at Banten Religious Court still tend to utilize the legal positivitistic considerations. Meanwhile, at the sociological level, it refers to the Article 5 of Law No. 48 of 2009 concerning Judicial Power stipulates that judges must explore, follow, and understand the legal values and society living law as as justice senses. The interpretation of this article depends on the custodian of hadanah towards the personality (morality) aspect. These includes moral and health aspects as well as the education and nurturing children opportunities aspects. Meanwhile, from the philosophical level, it is demonstrated by the law exploration derived from the Qur'an, Hadith, and fiqh principles that prioritize the children interests based on Maqasid al-Shariah.